(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
Waste dumping and its effects on public health and the environment have become significant concerns. This paper presents research conducted in two waste dumping sites in the Chittagong City Corporation area, Arefin nagar (Site 1) and Anondobazar (Site 2), to determine people’s perception of the environmental and health impacts of the landfill. Data were acquired using 250 pre-tested structured questionnaires (170 for the neighborhood and 80 for the working group). We conducted five key-informant interviews with officials from the Chittagong municipality and medical practitioners, along with four focus group discussions involving local residents and garbage workers to gather qualitative data. Descriptive statistics (frequency, percentages) were used for data analysis. Selected quantitative data was tested for significant associations using the Chi-squared test, and qualitative data was described using respondents’ narratives. The results suggest that most respondents were 26–35, illiterate, and worked in low-income jobs such as homemaking, small business, and day labour, reflecting landfill residents’ socioeconomic vulnerability. Residents complained of bad smells, soil fertility loss, and landfill leachate water contamination. Residents reported eye irritation (38.2%), hepatitis (27.9%), and headaches (23.5%). In contrast, waste collectors indicated frequent headaches (51.3%), skin conditions (43.6%), and nausea (42.1%). This underscores considerable risks to public health. Children exhibited notable susceptibility, with documented rates of vomiting at 67.6%, diarrhoea at 62.9%, and respiratory difficulties at 58.8%. The presence of disease vectors such as flies, mosquitoes, and rats near landfills has increased health risks. This investigation emphasises the necessity for improved waste management practices, such as establishing sanitary landfills and relocating dumping sites, while incorporating community feedback to shape inclusive landfill policies in urban Bangladesh. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 33-48